EFL STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF CANVA AS LEARNING MEDIA - Gito, Danissa Fitriamalia; Martriwati, Martriwati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The development of times goes alongside the improvement of technology. Appropriate learning media is needed that a teacher can apply to students in class. In this case, Canva was chosen as classroom learning media. This research aimed to know the perceptions of 11th grade student of one of the public high schools in Bekasi students concerning the usage of Canva app as a teaching and learning media in English class. This research is a Quantitative method research. Quantitative data was obtained by using a questionnaire. The research sample was 75 students (N = 75) out of 370 students. After the data is obtained, the data is calculated with statistical calculations by finding the mean, median, mode and standard deviation values through the SPSS application. After that, the data was analyzed by descriptive analysis method. It was discovered that every statement derived from the student questionnaire responses fell into the "very good" category. Canva is an useful dan easy to use as an application to be a learning media in English classroom and students felt satisfy with the canva as a learning media in English class which it is related to satisfaction with the ease and ease of use of the canva application.